Count them one by one : Black Mississippians fighting for the right to vote - Martin, Gordon A. (Margaret Walker Alexander series in African American studies., 2010)
Forrest County, Mississippi, became a focal point of the civil rights movement when, in 1961, the United States Justice Department filed a lawsuit against its voting registrar Theron Lynd. While thirty percent of the county's residents were black, only twelve black persons were on its voting rolls. United States v. Lynd was the first trial that resulted in the conviction of a southern registrar for contempt of court. The case served as a model for other challenges to voter discrimination in the South, and was an important influence in shaping the Voting Rights Act of 1965. Count Them One by One is a comprehensive account of the groundbreaking case written by one of the Justice Department's trial attorneys. Gordon A. Martin, Jr., then a newly-minted lawyer, traveled to Hattiesburg from Washington to help shape the federal case against Lynd. He met with and prepared the government's sixteen black witnesses who had been refused registration, found white witnesses, and was one of the lawyers during the trial. Decades later, Martin returned to Mississippi and interviewed the still-living witnesses, their children, and friends. Martin intertwines these current reflections with commentary about the case itself. The result is an impassioned, cogent fusion of reportage, oral history, and memoir about a trial that fundamentally reshaped liberty and the South.